Environment based clustering : A new approach - Lanzarini, Laura Cristina; De Giusti, Armando Eduardo (2000)
There is a vkiety of problems that require an automatic classification of a set of data. In this sense, clustering techniques have been widely applied, since they are known for forming classes or groups using a predefined similarity measure. This paper defines a new method which, as opposed to the solutions found so far, does not require any previous information about the data to be classified. The performance of this new proposal has been compared with a winner-take-all type method (WTA), which is widely used in clustering processes, and with the CDL method (Torbjom, 1998), with satisfactory results. -- Kewords: Clustering Techniques - Image Segmentation - Classification.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 06/03/2009)
Proceedings of the First International Workshop on Image and Signal Processing and Analysis, June 14-15, 2000, Pula, Croatia.
Keywords: CLUSTERING; RECONOCIMIENTO DE PATRONES